(untitled) (KONFERENSIYA, 2025)
This paper presents the thorough discussion of the simultaneous translation as a specific form of interlingual communication with references to cognitive, technical, professional, and ethical aspects. Based on empirical studies and theories of understanding the studies, the article follows the historical evolution of simultaneous translation since its initial discovery in the Nuremberg Trials up to its technological mediated versions. The discussion will examine the demanding nature of the cognitive requirements of interpreters such as multitasking requirements, working memory limitations and ear-voice span management